The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1002/hep.510240313
|View full text |Cite
|
Sign up to set email alerts
|

The role of gallbladder emptying in gallstone formation during diet-induced rapid weight loss

Abstract: nized factors in cholesterol gallstone formation; bile which is Obese persons are at risk for cholesterol gallstones saturated with cholesterol is essential for crystals to form, because their bile is saturated with cholesterol. The risk nucleation factors can influence whether crystals form in satincreases during rapid weight loss by means of certain urated bile, and gallbladder stasis can allow crystal growth. very-low-calorie diets or gastric bypass surgery. GallObesity is associated with increased bile cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(38 citation statements)
references
References 30 publications
0
37
0
1
Order By: Relevance
“…Thus, the risk for gallstones is substantially increased in these patients [106] that might be further increased by higher levels of DCA by impaired intestinal motility [107, 108]. For the prevention of gallstone development by gallbladder dysmotility, CCK injections have been recommended in patients receiving long‐term TPN [109], and small fat containing meals during weight reducing diets [110]. Recent study in mice showed that fibroblast growth factor 15 (FGF‐15; human homologue, FGF‐19), a hormone made by the distal small intestine in response to bile acids suppressing Cyp7a1 in the liver [111] as a counter player of CCK also controls gallbladder filling [112].…”
Section: Gallbladder Hypomotilitymentioning
confidence: 99%
“…Thus, the risk for gallstones is substantially increased in these patients [106] that might be further increased by higher levels of DCA by impaired intestinal motility [107, 108]. For the prevention of gallstone development by gallbladder dysmotility, CCK injections have been recommended in patients receiving long‐term TPN [109], and small fat containing meals during weight reducing diets [110]. Recent study in mice showed that fibroblast growth factor 15 (FGF‐15; human homologue, FGF‐19), a hormone made by the distal small intestine in response to bile acids suppressing Cyp7a1 in the liver [111] as a counter player of CCK also controls gallbladder filling [112].…”
Section: Gallbladder Hypomotilitymentioning
confidence: 99%
“…Rapid weight loss and weight cycling alter the ratio of cholesterol to bile salts in the gallbladder. This results from increased cholesterol mobilisation from peripheral tissue, coupled with increased hepatic synthesis of cholesterol [84,85,86]. Additionally, gallbladder motility is impaired, which leads to bile stasis and the formation of biliary sludge.…”
Section: Lifestyle Factorsmentioning
confidence: 99%
“…10, 11, 12, 13, 14 Later studies included VLCDs containing higher fat content (12–30 g per day), 21, 22, 23, 24 two of which were randomized controlled trials. 21, 22 None developed systematic gallstones in the high-fat group in either of the studies, suggesting that an adequate fat intake reduces gallstone formation. The fat content of the VLCD in our study was 7–9 g per day, consistent with the 7 g per day recommendation given by the European SCOOP-report on VLCD use.…”
Section: Discussionmentioning
confidence: 99%